Strengthening State Civil Apparatus Competency through a Coaching-Based Development Model: Evidence from Sukabumi City Government - Nur Soffa; Listiani, Teni; Afandi, Muhamad Nur; Rahman, Abdul (Universitas Muhammadiyah Pontianak, 2026)
This study examines the implementation of coaching as a non-classical competency development method for the State Civil Apparatus (ASN) in Sukabumi City Government and proposes an improved coaching-based model. Using a qualitative approach, data were collected through interviews, observations, and document analysis involving policymakers and ASN participants. Although formally introduced in 2019, coaching remains administrative and misaligned with the GROW framework, with unclear goals, limited exploration, coach dominance, and weak follow-up. Consequently, its impact on performance is limited. This study proposes a modified GROW-based model integrating preparation, structured dialogue, and systematic monitoring to enhance sustainable competency development and organizational performance.